Optimasi Operasi Embung Banyudono di Kabupaten Magetan Propinsi Jawa Timu - Prabowo, Sasongko Hari (Jurusan Teknik Sipil, Fakultas Teknik , UGM, 2006)
Embung Banyudono was constructed for irrigation purpose, especially for supplying water during the dry season. Due to the small capacity of the storage and the use of pumps to supply irrigation demand, the reservoir capability is limited. Storage resource potency has not been utilized optimally because of Embung Banyudono limited capacity and release, as well as un-organized operation of the reservoir. A study of operating optimization of Embung Banyudono is required in order to optimally utilize water resource potency of the reservoir. This study uses simulation method of the reservoir operation. The method is used in order to obtain balance between water supply and demand. Inputs for this simulation are initial storage, inflow, irrigation water demand, and the reservoir characteristics. Simulation is taken using several alternatives with cultivation pattern and initiation. Results of the simulation from the alternatives are then compared to select the highest cultivation intensity. The most optimum reservoir operation alternative is chosen from the highest cultivation intensity of the alternatives. Output of the simulation model is the decision variable, which is the maximum field width to be planted in every cultivation period. Results of the study show that the highest cultivation intensity with a stable operation is 210.3%, with 46.933 ha field width for cultivation period I, 30.303 ha for cultivation period II, and 70 ha for cultivation period III. The optimum cultivation pattern is rice-rice-crop, using corn as the crop. Optimum cultivation initiation is December first period.